Biofertilizers from wastewater treatment as a potential source of mineral nutrients for growth of amaranth plants - Ferreira, Elisa Teófilo [UNESP]; Barrochelo, Sarah Corrêa [UNESP]; De Paula De Melo, Sarah [UNESP]; Araujo, Thainá [UNESP]; Xavier, Augusto Cesar Coelho [UNESP]; Cechin, Inês [UNESP]; Da Silva, Gustavo Henrique Ribeiro [UNESP] (Public Library of Science (PLoS), 2023)
Exploring alternative fertilizers is crucial in agriculture due to the cost and environmental impact of inorganic options. This study investigated the potential of sewage-derived biofertilizers on the growth and physiology of Amaranthus cruentus plants. Various treatments were compared, including control treatments with inorganic fertilizer and treatments with biofertilizers composed of microalgae, biosolids and reclaimed water. The following traits were investigated: photosynthetic pigments, gas exchange, growth, and leaf nutrient concentrations. The results showed that the concentrations of N, P, Cu, Fe Zn and Na nutrients, in the dry microalgae and biosolids, were quite high for the needs of the plants. The wet microalgae presented high concentration of Cu, Fe and Zn nutrients while reclaimed water contained high concentration of N, K, Ca and S. Na and Zn nutrients increased in the leaf of plants treated with dry microalgae and biosolid, respectively. At the beginning of the flowering phase, total chlorophyll and carotenoids contents were lower for plants grown with wet microalgae while for plants grown with higher doses of biosolid or reclaimed water total chlorophyll was increased, and carotenoids were not affected. Lower photosynthetic pigments under wet microalgae resulted in lower photosynthetic rates. On the other hand, amendments with dry microalgae and biosolid increased photosynthetic rates with the biosolid being the most effective. Higher applications of biosolid, wet and dry microalgae produced a considerable increase in shoot biomass of amaranth, with the dry microalgae being the most effective. Additionally, reclaimed water obtained after tertiary treatment of sewage with microalgae and biosolids applied alone showed promising effects on plant growth. Overall, these findings suggest that organic fertilizers derived from sewage treatment have the potential to enhance plant growth and contribute to sustainable agricultural practices. Copyright: